Плазмохімічна конверсія сірководню у контексті розвитку водневої енергетики - Знак, Зеновій Орестович (Національний технічний університет «Харківський політехнічний інститут», 2023)
Виконано дослідження плазмохімічного розкладу сірководню на установках різних типів та різної номінальної потужності. Установлено питомі енергетичні витрати на отримання водню як цільового продукту плазмолізу сірководню. Показано, що економічна ефективність процесу може бути суттєво збільшена за рахунок отримання разом із воднем додаткового продукту – сірки, зокрема такої її цінної модифікації, як полімерна.

A study of the plasma-chemical decomposition of hydrogen sulfide was carried out on installations of different types and different nominal power. The specific energy costs for obtaining hydrogen as the target product of hydrogen sulfide plasmolysis have been established. It is shown that the economic efficiency of the process can be significantly increased due to obtaining an additional product - sulfur, in particular, its valuable modification, such as polymer, together with hydrogen.
Plasmachemical conversion of hydrogen sulphide in the context of the development of hydrogen energy
Keywords: водень; плазма; плазмохімічний розклад; питомі витрати; hydrogen; plasma; plasma chemical decomposition; specific costs